2018
DOI: 10.22610/jebs.v10i1(j).2092
|View full text |Cite
|
Sign up to set email alerts
|

The Cognitive and Psychological Bias in Investment Decision-Making Behavior: (Evidence From Indonesian Investor's Behavior)

Abstract: The purposes of this research were to understand and analyze the behavior of the psychological bias experienced by investors in making investment decisions. Psychological bias experienced by investors led to wrong decision making and fatal losses. This research used qualitative interpretive phenomenology method to understand the phenomenon of decision making based on the perspective of investors. The result showed that: (1) The phenomenon of cognitive bias and psychological bias behavior occur in nearly all in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…This Literature review therefore is organized to cover following factors impacting risk determinants of equity investment of different aspects of risk: a) Risk management including behavioral aspects, e.g., cognitive, and socio-cultural hypotheses [1]- [9] b) Financial statements related factors, i.e., critical financial statement ratios [6], [10]- [30] c) Macro-economic factors, Volatility, and returns correlation and causation [31]- [43] d) Management theories, Behavioral and mental models and other factors to assess fundamentals of business, competition, and longevity of growth [44]- [66], [67] e) Forecasting and ML techniques in price clustering, predictions and classification to support risk decisions using different models e.g. ARIMA, LSTM, VAR, Facebook Prophet, ARCH and GARCH family models etc.…”
Section: Page 86mentioning
confidence: 99%
See 2 more Smart Citations
“…This Literature review therefore is organized to cover following factors impacting risk determinants of equity investment of different aspects of risk: a) Risk management including behavioral aspects, e.g., cognitive, and socio-cultural hypotheses [1]- [9] b) Financial statements related factors, i.e., critical financial statement ratios [6], [10]- [30] c) Macro-economic factors, Volatility, and returns correlation and causation [31]- [43] d) Management theories, Behavioral and mental models and other factors to assess fundamentals of business, competition, and longevity of growth [44]- [66], [67] e) Forecasting and ML techniques in price clustering, predictions and classification to support risk decisions using different models e.g. ARIMA, LSTM, VAR, Facebook Prophet, ARCH and GARCH family models etc.…”
Section: Page 86mentioning
confidence: 99%
“…Psychological bias experienced by investors led to wrong decision making and fatal losses. The number of empirical evidences suggest that cognitive bias and psychological bias behavior occur in nearly all informants however at the same time undertaking a systematic approach, experience and insight of capital markets and awareness of existing bias reduce bias behavior that could be raising the return [67].…”
Section: Srinivas Publicationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, investors will overestimate their ability to evaluate the company as a potential investment [25], [16], [17], [26]. Overconfidence also causes investors to trade excessively (overtrading) and underestimates the risk [10], [11], [12], [13], [14]. As a result, it can produce a portfolio that cannot have low-performance expectations [27], and it can lead to gambling [28] .…”
Section: Investor Bias Behavior a Overconfidencementioning
confidence: 99%
“…Many studies have shown that investment managers or CEOs experience overconfidence and cognitive dissonance in managing investment funds [4], [5], [6], [7], [8], [9]. Overconfidence is excessive confidence, where an investor or investment manager feels better than others (better than average) [10], [11], [12], [13], [14], [15]. Overconfident managers tend to make high-risk investments for their customers without realizing it [9].…”
Section: Introductionmentioning
confidence: 99%